1999
DOI: 10.1017/s0033291798007776
|View full text |Cite
|
Sign up to set email alerts
|

A date to remember: the nature of memory in savant calendrical calculators

Abstract: A general mnemonic advantage cannot explain savant date calculation skills. Rather, through exposure to date information, the savants are suggested to develop a structured calendar-related knowledge base with the process of calculation utilizing the interrelations within this knowledge store. The cognitive processing style characteristic of autism may also play a role in the acquisition of this savant ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 42 publications
(46 reference statements)
2
61
0
2
Order By: Relevance
“…This suggests that the calculators must encode date information unusually effectively, rather than having increased memory capacity. Furthermore in another study reported by Heavey et al (1999), calculation facilitated memory retrieval suggesting that, as in language studies (e.g. Slamecka & Graf, 1978), active processing produces more accessible memories compared with passive learning conditions.…”
Section: Number and Calendar Calculatorsmentioning
confidence: 70%
See 3 more Smart Citations
“…This suggests that the calculators must encode date information unusually effectively, rather than having increased memory capacity. Furthermore in another study reported by Heavey et al (1999), calculation facilitated memory retrieval suggesting that, as in language studies (e.g. Slamecka & Graf, 1978), active processing produces more accessible memories compared with passive learning conditions.…”
Section: Number and Calendar Calculatorsmentioning
confidence: 70%
“…Miller, 1989;Sloboda, Hermelin & O'Connor, 1985;Young & Nettlebeck, 1994), linguistic ability (Smith & Tsimpli, 1991;Dowker, Hermelin & Pring, 1996), calendar calculation (giving the correct day of the week that corresponds to a particular date), (Heavey, Pring & Hermelin, 1999), arithmetical calculation (Anderson, O'Connor & Hermelin, 1999), or drawing ability (e.g. Selfe, 1977;Pring & Hermelin, 1997).…”
Section: Savant Talentmentioning
confidence: 99%
See 2 more Smart Citations
“…For calendar calculation, Heavey et al (1999) suggest that the calendars can be broken down into 'fragments' of dates. Combining the natural tendency to segment large chunks of information with idiosyncratic interest in dates, calendar calculation skills may emerge.…”
Section: Introductionmentioning
confidence: 99%